2008
DOI: 10.1016/j.brainres.2008.02.048
|View full text |Cite
|
Sign up to set email alerts
|

Changes in osmolality modulate voltage-gated calcium channels in trigeminal ganglion neurons

Abstract: Voltage-gated calcium channels (VGCCs) participate in many important physiological functions. However whether VGCCs are modulated by changes of osmolarity and involve in anisotonicityinduced nociception are still unknown. For this reason by using whole cell patch clamp techniques in rat and mouse trigeminal ganglion (TG) neurons we tested the effects of hypo and hypertonicity on VGCCs. We found that high voltage-gated calcium current (I HVA ) was inhibited by both hypo and hypertonicity. In rat TG neurons, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…TRPV4 is highly expressed in bronchial smooth muscle, where it is thought to contribute to Ca 2+ mobilization (Jia et al, 2004). TRPV4 was reported to be activated (Chen et al, 2008a), or at least potentiated (Güler et al, 2002), by hypoosmolar solutions. Because individuals with asthma produce copious amounts of airway secretions with low osmolarity, one attractive hypothesis for further exploration is that activation of TRPV4 by hypo-osmolar secretions in bronchial smooth muscle is a major cause of bronchoconstriction in these patients (see Liedtke and Simon, 2004).…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 99%
“…TRPV4 is highly expressed in bronchial smooth muscle, where it is thought to contribute to Ca 2+ mobilization (Jia et al, 2004). TRPV4 was reported to be activated (Chen et al, 2008a), or at least potentiated (Güler et al, 2002), by hypoosmolar solutions. Because individuals with asthma produce copious amounts of airway secretions with low osmolarity, one attractive hypothesis for further exploration is that activation of TRPV4 by hypo-osmolar secretions in bronchial smooth muscle is a major cause of bronchoconstriction in these patients (see Liedtke and Simon, 2004).…”
Section: B Transient Receptor Potential Channels Inmentioning
confidence: 99%
“…Like TRPV1, TRPV4 is modulated by CaM and ATP, C-terminal CaM binding potentiating the current (Strotmann et al, 2003) and Ca 2ϩ -dependent CaM binding to the N terminus desensitizing the current (Rosenbaum et al, 2004;Lishko et al, 2007). A variety of kinases also seem to modulate its activity (Gao et al, 2003;Chen et al, 2008a;Fan et al, 2009;Wegierski et al, 2009).…”
Section: A Transient Receptor Potential V1-v4 Subgroupmentioning
confidence: 99%
“…It has been reported that TRPV4 is involved in the modulation of VSGCs (TTX-R and TTX-S) in TG neurons through the regulation of various intracellular signaling pathways [15,16]. In addition to VGSCs, voltage-gated potassium and calcium channels, TRPV1, and glutamate receptors are also modulated by TRPV4 activation [9,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%